Inorganic Hollow Nanocoils Fabricated by Controlled Interfacial Reaction and Their Electrocatalytic Properties. Issue 44 (24th September 2021) - Moon, Jun Hwan; Lee, Moo Young; Park, Bum Chul; Jeon, Yoo Sang; Kim, Seunghyun; Kim, Taesoon; Ko, Min Jun; Cho, Kang Hee; Nam, Ki Tae; Kim, Young Keun
Abstract: The fabrication of 3D hollow nanostructures not only allows the tactical provision of specific physicochemical properties but also broadens the application scope of such materials in various fields. The synthesis of 3D hollow nanocoils (HNCs), however, is limited by the lack of an appropriate template or synthesis method, thereby restricting the wide‐scale application of HNCs. Herein, a strategy for preparing HNCs by harnessing a single sacrificial template to modulate the interfacial reaction at a solid–liquid interface that allows the shape‐regulated transition is studied. Furthermore, the triggering of the Kirkendall effect in 3D HNCs is demonstrated. Depending on the final state of the transition metal ions reduced during the electrochemical preparation of HNCs, the surface states of the binding anions and the composition of the HNCs can be tuned. In a single‐component CrPO4 HNC with a clean surface, the Kirkendall effect of the coil shape is analyzed at various points throughout the reaction. The rough‐surface multicomponent MnO x P0.21 HNCs are complexed with ligand‐modified BF4 ‐Mn3 O4 nanoparticles. The fabricated nanocomposite exhibits an overpotential decrease of 25 mV at neutral pH compared to pure BF4 ‐Mn3 O4 nanoparticles because of the increased active surface area. Abstract : An electrochemical strategy for fabricating 3d metal‐based hollow nanocoils using electrodeposited nanocoils as a sacrificial template is demonstrated. The reduction pathway of ionic complexes in the colloidal reaction solution influences the surface conditions and composition of the synthesized hollow nanocoils. The manganese nanoparticle–hollow nanocoil composite expands the active area and shows improved catalytic efficiency for the oxygen evolution reaction.